Effects of niobium (Nb) on mechanical properties of laser coated nitinol (NiTi) used for surface modification of Ti6Al4V alloy - Skhosane, Besabakhe Samuel (My University, 2021)
In the present study, mechanically pre-alloyed powders consisting of niobium, titanium and nickel were deposited onto Ti6Al4V substrate to form a coating with the aim of improving surface wear resistance. Laser cladding was used to melt the injected powder to form a coating on the surface of the substrate. Fabricated samples were produced from the powder mixture of Ti55Ni45, Ti53.75Ni43.75Nb2.5,Ti52.5Ni42.5Nb5 and Ti51.25Ni41.25Nb7.5 using different laser power (600W and 1000W) and laser-scanning speed (0.5-1m/min)at fixed powder deposition rate of 2rev/min. The fabricated samples were characterised using optical microscopy (OM), scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS), differential scanning calorimeter (DSC), X-ray diffraction (XRD), micro hardness tester and wear tester. The produced coatings were well bonded and consisted of globular and dendritic structure with intermetallic phases such as NiTi and NiTi2. Hardness decreased with an increase in niobium content while wear resistance enhanced, with no cracking on the coating surface as niobium content increased
A research report submitted to the School of Chemical and Metallurgical Engineering, Faculty of Engineering and the Built Environment, University of the Witwatersrand, in the fulfilment of the requirement for the degree of Master of Science in Engineering